Speed Control of 3-phase Induction Motors under Fault Conditions Supplied by Wind Turbine Using Indirect Vector Control - Mohammad Jannati; Solieman Eskandari; Tole Sutikno (Institute of Advanced Engineering and Science, 2017)
This article studies speed control of 3-phase Induction Motors (IMs) under fault conditions supplied by wind turbine using Indirect Vector Control (IVC). The wind turbine plays as a prime mover to a connected DC generator. Pulse Width Modulation (PWM) is used to obtain 3-phase AC voltage from the DC generator output. The proposed modified controller is able to control a star-connected 3-phase IM under normal, stator winding open-circuit fault and speed-sensor fault conditions. Simulation results are presented and shown the performance, validity and possibility of the proposed technique. The results demonstrate that, the proposed scheme provides good dynamic performance especially in reduction of IM speed and torque pulsations.